2019
DOI: 10.15252/embj.2018100276
|View full text |Cite
|
Sign up to set email alerts
|

Collided ribosomes form a unique structural interface to induce Hel2‐driven quality control pathways

Abstract: Ribosome stalling triggers quality control pathways targeting the mRNA (NGD: no‐go decay) and the nascent polypeptide (RQC: ribosome‐associated quality control). RQC requires Hel2‐dependent uS10 ubiquitination and the RQT complex in yeast. Here, we report that Hel2‐dependent uS10 ubiquitination and Slh1/Rqt2 are crucial for RQC and NGD induction within a di‐ribosome (disome) unit, which consists of the leading stalled ribosome and the following colliding ribosome. Hel2 preferentially ubiquitinated a disome ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
500
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 268 publications
(544 citation statements)
references
References 54 publications
41
500
3
Order By: Relevance
“…We processed the data using the 80S extension approach as described previously and segregated classes of ribosomal particles stalled in the POST and PRE states (Appendix Fig S9). These collided disomes, which were composed of two POST state ribosomes, are thus strikingly different from previously characterized disomes in both mammalian and yeast systems (Juszkiewicz et al, 2018;Ikeuchi et al, 2019). These collided disomes, which were composed of two POST state ribosomes, are thus strikingly different from previously characterized disomes in both mammalian and yeast systems (Juszkiewicz et al, 2018;Ikeuchi et al, 2019).…”
Section: Ribosome Collisions On Poly(a) Tracts Affect Disome Formationcontrasting
confidence: 75%
See 2 more Smart Citations
“…We processed the data using the 80S extension approach as described previously and segregated classes of ribosomal particles stalled in the POST and PRE states (Appendix Fig S9). These collided disomes, which were composed of two POST state ribosomes, are thus strikingly different from previously characterized disomes in both mammalian and yeast systems (Juszkiewicz et al, 2018;Ikeuchi et al, 2019). These collided disomes, which were composed of two POST state ribosomes, are thus strikingly different from previously characterized disomes in both mammalian and yeast systems (Juszkiewicz et al, 2018;Ikeuchi et al, 2019).…”
Section: Ribosome Collisions On Poly(a) Tracts Affect Disome Formationcontrasting
confidence: 75%
“…Interestingly, when studying ribosomal collisions as a consequence of poly(A)-mediated stalling, we found a large fraction of the disomes in a novel POST-POST state that was distinct from the previously characterized disome structures in both mammalian and yeast systems (Fig 6A and B; Juszkiewicz et al, 2018;Ikeuchi et al, 2019). Interestingly, when studying ribosomal collisions as a consequence of poly(A)-mediated stalling, we found a large fraction of the disomes in a novel POST-POST state that was distinct from the previously characterized disome structures in both mammalian and yeast systems (Fig 6A and B; Juszkiewicz et al, 2018;Ikeuchi et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Here, Ikeuchi et al (2019) demonstrated that Hel2-mediated ubiquitination of collided ribosomes act as a master regulator for both processes of NGD and RQC. Here, Ikeuchi et al (2019) demonstrated that Hel2-mediated ubiquitination of collided ribosomes act as a master regulator for both processes of NGD and RQC.…”
mentioning
confidence: 86%
“…How these two processes are triggered by the same molecular signal is not obvious. The new results from the Inada and Beckmann groups in this issue (Ikeuchi et al, 2019) now provide compelling evidence suggesting that ribosomal protein ubiquitination by Hel2 is required for both processes. It is thus likely that ubiquitination of ribosomal proteins is the first reaction to proceed after stalling has occurred, and is utilized by all downstream events to manifest the different facets of NGD and RQC.…”
mentioning
confidence: 89%